Maciunas : Eccentric Artist and Seminal Influence - Wilmer, Stephen Elliot (Nordic Theatre Studies, 2022)
Fluxus was an inspirational movement based in New York in the 1960s that consisted of a group of more than fifty loosely connected artists from various disciplines, who made significant experiments to develop music, conceptual art, visual art, performance art, video, and film. They participated in eclectic concerts, media, performative events, and installations in the USA and Europe. In this paper, I want to examine how George Maciunas, a Lithuanian exile and its nominal organiser, had a seminal influence on avant-garde art in America and Europe and, despite avowing an open attitude towards what could be art, he also enforced draconian ideas about what could be included and what could not. In particular I want to emphasize his influence in Scandinavia because most of the literature on Fluxus has focused on his work in the USA and Germany.